Influence of passive deformation in the lift coefficient of a NACA0012 wing model - Durán, E.; Lorite Díez, M.; Konovalov-Shishov, Nikita; Gutiérrez Castillo, P.; Del-Pino-Peñas, Carlos Manuel (Elsevier, 2024)
The extensive use of lightweight materials in aerial vehicle wings involves structural flexibility phenomena that generate non-negligible deformation effects. This influence is not restricted to big aircraft but also plays a role in smaller aeroplanes and Unmanned Aerial Vehicles (UAVs). Here, we conduct wind tunnel experiments to analyze the effect of passive deformation on the wing model lift slopes. To isolate the deformation effect, we compare rigid wings with a NACA0012 airfoil imposing a prescribed spanwise deformation. We study three levels of deformation: non-deformed, around 2% and 4.5% of tip deflection. Also, we consider the effect of the wing length by using three different semi-aspect ratios (1, 2, and 4), so a total of nine rigid wing models have been analyzed for a range of Reynolds number from to . Deformed wing models show an increase in lift coefficient compared to non-deformed wing cases. Both deformation levels exhibit a qualitatively similar lift increment. A correlation to predict lift coefficient slope in a flat plate is adapted for a NACA0012 airfoil and validated using our experimental results and literature data. The adjusted correlation can quantify the deformation effect on the lift slope, which is comparable to using a slightly longer wing model.
Hightlights The deformed NACA0012 wing models show a lift increase over the non-deformed cases. The lift slope of NACA0012 wing models are predicted using a flat plate correlation. The fitted correlation quantifies the effect of deformation on the lift slope.
Keywords: Ingeniería aeronáutica; Aviones-Alas; NACA0012; Deformaciones (Mecánica); Túneles de viento-Experimentación; Coeficiente de sustentación; Lift coefficient; Passive deformation; NACA0012; Aspect ratio